Ceramide as a Mediator of Non-Alcoholic Fatty Liver Disease and Associated Atherosclerosis - Kasumov, Takhar; Li, Ling; Li, Min; Gulshan, Kailash; Kirwan, John P.; Liu, Xiuli; Previs, Stephen; Willard, Belinda; Smith, Jonathan D.; McCullough, Arthur (PloS one, 2015)
Cardiovascular disease (CVD) is a serious comorbidity in nonalcoholic fatty liver disease (NAFLD). Since plasma ceramides are increased in NAFLD and sphingomyelin, a ceramide metabolite, is an independent risk factor for CVD, the role of ceramides in dyslipidemia was assessed using LDLR(-/-) mice, a diet-induced model of NAFLD and atherosclerosis. Mice were fed a standard or Western diet (WD), with or without myriocin, an inhibitor of ceramide synthesis. Hepatic and plasma ceramides were profiled and lipid and lipoprotein kinetics were quantified. Hepatic and intestinal expression of genes and proteins involved in insulin, lipid and lipoprotein metabolism were also determined. WD caused hepatic oxidative stress, inflammation, apoptosis, increased hepatic long-chain ceramides associated with apoptosis (C16 and C18) and decreased very-long-chain ceramide C24 involved in insulin signaling. The plasma ratio of ApoB/ApoA1 (proteins of VLDL/LDL and HDL) was increased 2-fold due to increased ApoB production. Myriocin reduced hepatic and plasma ceramides and sphingomyelin, and decreased atherosclerosis, hepatic steatosis, fibrosis, and apoptosis without any effect on oxidative stress. These changes were associated with decreased lipogenesis, ApoB production and increased HDL turnover. Thus, modulation of ceramide synthesis may lead to the development of novel strategies for the treatment of both NAFLD and its associated atherosclerosis.